Localized eruptive porokeratosis in pediatric patients following treatment of acute leukemia. Issue 5 (21st August 2021) - Kang, Bianca Y.; Jacobsen, Jeffrey; Price, Harper N.; Andrews, Israel D.
Abstract: Porokeratosis is a rare diagnosis in the pediatric population, and eruptive disease has been documented prior in patients with history of stem cell transplantation. Comparing various porokeratosis eruptions between patients can be difficult due to limitations in current classification and nomenclature. Here, we discuss a single‐institution case series of three children who developed porokeratosis following hematopoietic stem cell transplantation for acute leukemia, and we propose that this presentation be termed localized eruptive porokeratosis (LEP). We present the distinguishing features of this variant by discussing the shortcomings in current nomenclature and also examine the association between porokeratosis and hematopoietic stem cell transplantation in the pediatric population.